Perancangan Data Warehouse Untuk Informasi Strategi Studi Kasus Penerimaan Siswa Baru STIE Binaniaga Bogor - Rahmat Tri Yunandar; Amir Amir; khairul rizal (Universitas Bina Sarana Informatika, 2020)
As an Educational institutions need to have more knowledge, in evaluating, designing and making decisions. Where from such knowledge can be obtained from the data stored in the operational activities of educational institutions databases into the data warehose, so it can be used as a support in the decision making process. Data Warehouse has a major role in the provision of strategic information that can be used to meet the needs of management in a business context. This study examines the development of the data warehouse to the data of new admissions to the STIE Binaniaga Bogor, which can dig up important information that can help retrieval strategic decision to support promotional activities at the STIE Binaniaga Bogor. The final goal of this study was to produce a design of a data warehouse that can support the needs of management in making decisions by providing strategic information on new admissions, which produces a summary of information that is accurate and useful as input to determine strategies for promotion.